2016
DOI: 10.1007/s00393-016-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 als Regulator der Autoinflammation bei rheumatischen Erkrankungen

Abstract: Caspase-1 is an integral regulator of the innate immune system. Its core functions are the processing and secretion of the proinflammatory cytokines interleukin 1β (IL-1 beta) and IL-18 and the initiation of proinflammatory cell death, which is referred to as pyroptosis. Activation of caspase-1 plays a pivotal role during immune defense mechanisms against infections by the innate immune system. Dysregulated activation of caspase-1 has been recognized to be involved in the pathophysiology of a constantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…Caspase-1 is a member of the Caspase family, and was the first to be identified ( 18 ). As the typical inflammation-associated Caspase, Caspase-1 is a key effector molecule during the inflammatory response, regulating the inflammatory reaction in the tumor microenvironment and the anti-tumor immunity of organisms ( 19 , 20 ). Recent studies demonstrated that Caspase-1 functions in apoptosis ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 is a member of the Caspase family, and was the first to be identified ( 18 ). As the typical inflammation-associated Caspase, Caspase-1 is a key effector molecule during the inflammatory response, regulating the inflammatory reaction in the tumor microenvironment and the anti-tumor immunity of organisms ( 19 , 20 ). Recent studies demonstrated that Caspase-1 functions in apoptosis ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is a novel cytokine with the similar structure of IL-1 and the analogous biological function of IL-12 [17]. Inactive IL-18 protein is cleaved by Caspase-1 to acquire activity and Caspase-1 has been found to regulate autoin ammation in the occurrence of rheumatic diseases, including AS [18]. In publication, IL-18 can facilitate Th1 cells to secret a number of cytokines, including IFN-γ, IL-2, GM-CSF and so on, and promote the proliferation of Th1 cells, too [19].…”
Section: Discussionmentioning
confidence: 99%
“…Differences between here presented data and previous observations may be explained with varying sensitivity between detection systems, since IL-1RA is usually considered a quite robust marker of inflammasome activation. In addition to IL-1β cleavage and activation, caspase-1 is also responsible for the activation of the pro-inflammatory cytokine IL-18 ( 14 , 15 ). IL-18 is expressed by monocytes, lymphocytes, eosinophils, mast cells, and others.…”
Section: Discussionmentioning
confidence: 99%